Using ESOPs to Democratize Labor-Based Platforms. Issue 1 (4th March 2022) - Gonza, Tej; Ellerman, David
Abstract: This paper explores a new strategy to address the problem of "gig-workers" in labor-based platform companies. The two current strategies are (1) regulations (e.g., requiring platforms to recognized workers as employees) or (2) creating new platform cooperatives to compete with the established platforms. The authors propose a third complementary approach, which is democratizing and adapting the Employee Stock Ownership Plan to gain co-ownership in the local subsidiaries of the labor-based platforms (LBP). This option puts a new tool in the hands of the municipal and national regulatory authorities.